2018
DOI: 10.1097/pai.0000000000000505
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mutation Rates of GNAQ or GNA11 in Cases of Uveal Melanoma in Japan

Abstract: GNAQ and GNA11 mutations are thought to be important for the tumorigenesis of uveal melanoma. Although previous studies have reported on mutation rates in cases of uveal melanoma, presently, no such report for the Japanese population exists. In this study, we examined the frequency of GNAQ and GNA11 somatic mutations in cases of uveal melanoma in Japan and their relationship with clinicopathologic features or Ki-67-positive cell rates (Ki-67 labeling index: Ki-67 LI) using immunofluorescence methods. The study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…It is unknown whether this is a result of inadequate study samples in previous research that limited the power of the statistical analysis. Ominato et al [34] found in 19 Japanese UM patients that the frequency of GNAQ and GNA11 was 57.9%. These mutation frequencies for GNAQ and GNA11 were obviously lower than ours although they were studied in an Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether this is a result of inadequate study samples in previous research that limited the power of the statistical analysis. Ominato et al [34] found in 19 Japanese UM patients that the frequency of GNAQ and GNA11 was 57.9%. These mutation frequencies for GNAQ and GNA11 were obviously lower than ours although they were studied in an Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…(2) The overall frequency of GNAQ/ GNA11 mutations in different populations is variable. Analyses of UM from Dutch, American, Japanese, Greek and Chinese populations reveal a frequency of GNAQ/GNA11 mutations of 93.4%, (23) 83.0%, (24) 57.9%, (25) 42.4% (26) and 38.0%, (27) respectively. The frequency of GNAQ/GNA11 mutations in the South Indian population has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In the scientific literature, the frequencies of GNAQ mutations have been reported to range from 24.2 to 53.3% and those of GNA11 mutations from 24.2 to 60% [20,[28][29][30][31]. In previous studies, non-Caucasian populations have shown reduced mutation frequencies in these two genes, but more recent studies have shown that mutations in this population may be closer to the frequencies previously mentioned [32,33]. This could indicate that ethnic and demographic variables could play important roles that are yet to be elucidated.…”
Section: Gna11 Genesmentioning
confidence: 72%
“…Mutational hotspots in both genes have already been described in the literature, characterised by the presence of activating missense variants that exclusively affect exons 4 and 5, and more specifically, the arginine 183 (R183) and glutamine 209 (Q209) codons. The majority of GNA11 mutations in codon 209 leads to glutamine to leucine (p.Q209L) and proline (p.Q209P) substitutions [20,29,32,34]. These mutations occur from one-base substitutions at codon 209 (CAG), with the most common substitutions of A > T (94.5%) and A > C (2.7%) [19].…”
Section: Gna11 Genesmentioning
confidence: 99%